Leveraging genetics to investigate causal effects of immune cell phenotypes in periodontitis: a mendelian randomization study - Bai, Yingjie; Xie, Pengxian; Jin, Ziyu; Qin, Shengao; Ma, Guowu (Frontiers in Genetics, 2024)
Introduction Immune cells are dynamic in the inflammatory environment and play a key role in eradicating periodontal pathogens, modulating immune responses, and instigating tissue destruction. Identifying specific immune cell phenotypes associated with periodontitis risk is essential for targeted immunotherapeutic interventions. However, the role of certain specific immune cell phenotypes in the development of periodontitis is unknown. Mendelian randomization offers a novel approach to reveal causality and address potential confounding factors through genetic instruments. Methods This two-sample Mendelian randomization study assessed the causal relationship between 731 immune cell phenotypes and periodontitis using the inverse variance weighting method with the GWAS catalog genetic database. Methodological robustness was ensured through Cochran’s Q test, MR-Egger regression, MR-PRESSO, and Leave-One-Out analysis. Results 14 immune cell phenotypes showed potential positive causal associations with periodontitis risk (p < 0.05), suggesting an increased risk, while 11 immune cell phenotypes exhibited potential negative causal associations (p < 0.05), indicating a reduced risk. No significant heterogeneity or pleiotropy was observed. Conclusion This study underscores certain immune cell types as potential periodontitis risk biomarkers, laying a theoretical foundation for future individualized treatment and precision medicine development.